2014
DOI: 10.1371/journal.pone.0090078
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Walking and Perceived Environment in Chinese Community Residents: A Cross-Sectional Study

Abstract: BackgroundThe neighborhood environment, as a determinant of walking, has been assessed in several developed countries. However, few studies have investigated these associations in Chinese populations.ObjectiveTo examine the association between the perceived neighborhood environment and walking for recreation or transportation purposes among Chinese community residents.MethodsWe used a multi-stage stratified random sampling design to conduct a cross-sectional study of 1528 Chinese adults in Shanghai. Environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…All levels of government including federal, state and local, assist client needs including mobility, transport and travel time (Bigotte and Antunes 2007;Bisht et al 2010), and the ability to accommodate new clients, affordability and acceptability in terms of attitudes and preferences (Penchansky and Thomas 1981). Accessibility models also produce health co-benefits derived with increased physical activity associated with the availability of local community services and neighbourhood facilities (King et al 2003;Pikora et al 2006;Leslie and Cerin 2008;Frank et al 2010;Salvador, Reis, and Florindo, 2010;Jia et al 2014;Koohsari et al 2015).…”
Section: Methods Used For Planning and Delivering Social Infrastructumentioning
confidence: 99%
“…All levels of government including federal, state and local, assist client needs including mobility, transport and travel time (Bigotte and Antunes 2007;Bisht et al 2010), and the ability to accommodate new clients, affordability and acceptability in terms of attitudes and preferences (Penchansky and Thomas 1981). Accessibility models also produce health co-benefits derived with increased physical activity associated with the availability of local community services and neighbourhood facilities (King et al 2003;Pikora et al 2006;Leslie and Cerin 2008;Frank et al 2010;Salvador, Reis, and Florindo, 2010;Jia et al 2014;Koohsari et al 2015).…”
Section: Methods Used For Planning and Delivering Social Infrastructumentioning
confidence: 99%
“…Perceived proximity to public services (e.g. stores, parks and transport stations) in suburban China (Shanghai) was associated with significantly increased odds for both transport and leisure walking [51]. Parra et al [33], however, did not show significant relationships between perceived presence of public services with a 10-min walk in urban Brazil and either transport or leisure walking, yet a significant positive association was found for transport cycling.…”
Section: Walking and Cyclingmentioning
confidence: 95%
“…Updating this literature review in Feb 2015, SB identified a small number of newer studies, corroborating the effect of the neighbourhood environment on walking for transport (Van Cauwenberg et al, 2014;Jia et al, 2014); of traffic on travel behaviour Tsunoda et al, 2012); and that transport problems can cause psychological distress (Taylor et al, 2012).…”
Section: Community Severance and Social Networkmentioning
confidence: 88%